A case series of efavirenz induced gynaecomastia - Teli, Balakrishna; Biradar, Sneha; S., Sheshan V. (International Journal of Advances in Medicine, 2021)
The prognosis of HIV infection has significantly changed following the introduction of highly active anti-retroviral therapy by reducing AIDS related morbidity and mortality. At the same time, HAART is documented for its side effects. Gynaecomastia is a less documented side effect of a commonly used ART drug efavirenz. There are only few case reports of HAART-induced gynaecomastia in resource limited settings. Initially gynaecomastia related to HAART in HIV patients was thought due to lipodystrophy and was termed as pseudogynaecomastia. Later, few case reports of efavirenz related gynaecomastia were published after ruling out other causes of gynaecomastia. All other causes of gynaecomastia were ruled out in our patients too. The incidence of gynaecomastia is increasing in men with HIV on HAART therapy, proper identification and management will promote better drug adherence. The present study presented a series of two cases that developed ultrasound confirmed gynaecomastia following efavirenz containing HAART.